2021
DOI: 10.3390/ijms22052449
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Adverse Drug Reactions in Janus Kinase (JAK) Inhibitors: Does the Inhibitor Specificity Play a Role?

Abstract: Recent advances in immunology enabled the characterization of several signal transmitting pathways responsible for proper cytokine and chemokine signaling. Among them, Janus kinases (JAKs) are essential components of receptor activation systems. The discovery of JAK kinases enabled the synthesis of JAK kinase inhibitors (JAKi or Jakinibs), which have proven to be efficacious in the treatment of hematologic malignancies and several rheumatological disorders and continue to be investigated in many clinical indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 150 publications
0
20
0
Order By: Relevance
“…Moreover, the underlying mechanism is still unclear due to a potential “Janus effect” of JAK inhibition that is responsible for a reduction in cytokine-driven thromboembolic events, but also for an increase in prothrombotic potential, as indicated by real-world evidence. There is uncertainty on whether or not selectivity versus JAK1 or JAK2 plays a critical role in risk modulation [ 55 ].…”
Section: Safety Issuesmentioning
confidence: 99%
“…Moreover, the underlying mechanism is still unclear due to a potential “Janus effect” of JAK inhibition that is responsible for a reduction in cytokine-driven thromboembolic events, but also for an increase in prothrombotic potential, as indicated by real-world evidence. There is uncertainty on whether or not selectivity versus JAK1 or JAK2 plays a critical role in risk modulation [ 55 ].…”
Section: Safety Issuesmentioning
confidence: 99%
“… Recent advances in kinase drug discovery span the drug discovery pipeline from target identification through to pharmacovigilance. These advances are illustrated in six primary research articles covering kinome array profiling [ 4 ], structure-guided drug development [ 5 , 6 ], rational computational design [ 7 ], targeting the protein/peptide substrate binding site [ 8 ] and combinatorial drug treatment [ 9 ]; and nine topical reviews on TAO kinases [ 10 ], liver disease [ 11 ], AMPK [ 3 ], pancreatic cancer [ 12 ], urothelial carcinoma [ 13 ], Flaviviridae infections [ 14 ], squamous cell carcinoma [ 15 ], thyroid cancer [ 16 ] and adverse reactions to JAK inhibitors [ 17 ]. The indicated figures from special issue papers have been re-used with permission from the authors.…”
mentioning
confidence: 99%
“…The drug discovery process does not end with regulatory approval; monitoring for adverse effects continues once a drug has reached the market ( Figure 1 ). As an example of the importance of this ongoing monitoring, Kotyla and co-authors [ 17 ] review the literature linking cytokine signalling to pro-thrombotic signalling with a view to illuminating mechanistic links underlying the clinically observed increased risk of thromboembolism in patients treated with inhibitors of the Janus kinase (JAK) family (Jakinibs). Their task is complicated both by the lack of selectivity of the currently approved Jakinibs, and the complex network linking cytokines via their receptors to downstream JAK activity.…”
mentioning
confidence: 99%
“…Moura et al correctly point out the inhibition of JAK2 mutations could reduce the risk of thrombosis. However, some cytokines related to thrombosis and inflammation use different JAK pairings for signal transduction; for example, prothrombotic and anti-thrombotic signals are transmitted, respectively, by JAK1/TYK2 and JAK1/JAK2 [ 13 ]. Baricitinib, a selective JAK1/2 inhibitor, has shown a dose-dependent increase in platelets [ 14 ].…”
mentioning
confidence: 99%
“…Baricitinib inhibition of JAK2 associated with thrombopoietin receptors in platelets and megakaryocytes may alter platelet homeostasis leading to thrombocytosis [ 15 , 16 ]. Finally, a recent study showed that baricitinib down-regulated IL-6- and IL-12-dependent inflammatory pathways, but left interferon levels unaffected, which may transmit the strongest prothrombotic signals [ 17 ].The imbalance in thrombotic events with baricitinib 4-mg dose in clinical trials [ 13 ] prompted the FDA to approve the lower 2-mg dose in patients with rheumatoid arthritis.…”
mentioning
confidence: 99%